Heart rate cost as a tool for monitoring recovery between acute training sessions - Souto Filho, Jose Morais; De Moraes, Milton Rocha; De Araujo Leite, Patricio Lopes; Alves Maciel, Larissa; Candida Arruda Andrade Rezende, Andrea; Dos Santos Rosa, Thiago; Andrade Machado, Fabiana; Rodrigues Moreira, Sergio; Yukio Asano, Ricardo; Magalhaes Sales, Marcelo; Simoes, Herbet Gustavo (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Effective recovery monitoring is crucial to optimise performance and prevent overreaching, injuries, and over-training. This study evaluated the heart rate cost (HRC) during submaximal running as a simple, non-invasive, and cost-effective tool to assess recovery after a high-intensity training session.Methods. Fifteen male recreational runners (aged 18–31 years) participated in this investigation. Assessments included anamnesis, blood tests (CPK, cortisol, testosterone), body composition analysis, blood pressure, heart rate (HR), heart rate variability (HRV), pain scale, vertical jump (VJ), and a 6-minute submaximal running test to determine HRC (HR/running velocity). Afterwards, participants completed a high-intensity training session, consisting of six 1-minute treadmill runs and 10 strength exercises in a circuit format.Results. HRC increased 24 h post-training, indicating higher physiological cost, but significantly decreased after five days of recovery (p = 0.044). VJ performance returned to normal after five days compared to 24 h post-training (p = 0.013), with a significant correlation between the delta reduction in HRC and performance recovery on VJ (r = –0.689). No significant changes were found in the testosterone/cortisol ratio or HRV (HRV) (p > 0.05), likely due to the fact that these variables reflect chronic stress more than acute stress. CPK levels mirrored HRC and VJ trends, worsening 24 h post-training and improving after five days (p = 0.01).Conclusions. HRC proved effective in distinguishing recovery status after high-intensity training, showing sensitivity comparable to VJ and CPK measurements. These findings are relevant for researchers, coaches, and athletes in daily re-covery assessments.
Keywords: HR cost of running; cortisol; creatine phosphokinase (CPK); HR variability (HRV); vertical jump